PERANCANGAN APLIKASI GENERAL LEDGER MENGGUNAKAN FRAMEWORK CODEIGNITER PADA PT. FAJAR PANGAN LESTARI - Sutanto Sutanto; Ahmad Fatoni (LPPM Unbaja, 2022)
PT. Fajar Pangan Lestari is a company engaged in the Unilever distributor that has a financial activity, at this time the recording of financial activities is still done manually or handwritten which is less effective and less efficient in the recording process, this will complicate the process of creating an account automatically. details, looks for daily cash statement transactions and allows errors in recording debit or credit. Therefore, an application is made that can manage accounts in detail, process transaction searches efficiently and group debit credits in a balanced way for a transaction. This application is made using Codeigniter Framework and MySQLI as database processing software. This application is also designed using UML (Unified Modeling Language) and waterfall as a system development method with the stages of needs analysis, system design, program code writing, application testing. The conclusion from this research is that this system makes it easier for companies to make more effective daily reports, grouping debit credit transactions more effectively and the accounts needed for more detailed transactions